1999
DOI: 10.1002/(sici)1522-726x(199903)46:3<357::aid-ccd23>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in ischemic vascular complications with a hydrophilic-coated intra-aortic balloon catheter

Abstract: Hydrophilic coatings improve the handling characteristics of angioplasty equipment, but until recently this technology has not been available for intra‐aortic balloon (IAB) catheters. To determine whether a new hydrophilic coating is associated with a reduction in IAB‐related complications, we prospectively evaluated 188 patients undergoing insertion of this new IAB catheter. Complications related to IAB insertion were recorded and compared to data from 682 patients previously treated with an uncoated IAB cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The major finding of this study is that the incidence of major balloon-related complications is encouragingly low (2.8%). Advances such as percutaneous insertion and smaller-diameter catheters have considerably reduced the incidence of serious vascular complications (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the incidence of unsuccessful IABP due to balloon leak, poor inflation, poor augmentation or insertion difficulty was extremely low (2.3%), and to our knowledge, no previous study has examined this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding of this study is that the incidence of major balloon-related complications is encouragingly low (2.8%). Advances such as percutaneous insertion and smaller-diameter catheters have considerably reduced the incidence of serious vascular complications (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the incidence of unsuccessful IABP due to balloon leak, poor inflation, poor augmentation or insertion difficulty was extremely low (2.3%), and to our knowledge, no previous study has examined this issue.…”
Section: Discussionmentioning
confidence: 99%
“…These coatings are for instance applied to angioplasty catheters for reduction of the coefficient of friction during transfer to the stenotic vessel [6]. As the spontaneous drug transfer from the so-called drug-coated balloons (DCB) is already applied as a therapeutic alternative to DES [7,8], the development of hydrophilic coating with LDD function would be of high interest for this application.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies performed during the late 1980s, the incidence of severe limb ischemia was reported to be 8.3-11.7% 1,10-13 ; however, in the late 1990s, the incidence was reported to have reduced to 3.3-4.0%. [14][15][16] More recently, a study that compared the outcome between patients who underwent IABP with 8 and 9.5 Fr catheters showed that the 8 Fr IABP catheter was superior to the 9.5 Fr catheter regarding the incidence of limb ischemia. 4 In fact, no patients in this study (n = 69) experienced limb ischemia, whereas seven patients treated with 7 or 7.5 Fr IABP catheter during the same period developed limb ischemia (n = 165).…”
Section: Discussionmentioning
confidence: 99%